2015
DOI: 10.1039/c5ay01667c
|View full text |Cite
|
Sign up to set email alerts
|

An eco-friendly cellular phase microextraction technique based on the use of green microalgal cells for trace thallium species determination in natural water samples

Abstract: The selective biosorption of Tl(iii) species on green microalgal cells as a fundamental strategy for developing an efficient microextraction procedure for trace Tl speciation analysis in water samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Nielsen et al (2005) proposed the global average Tl range of 6±4 ng L -1 , based on analyses in 12 large rivers. Other studies reported various Tl concentration ranges in freshwater ecosystems, for example 5-17 ng L -1 in river waters in Poland (Karbowska 2016), 2-443 ng L -1 in United Kingdom(Law and Turner 2011) , about 13 ng L -1 in a river whose catchment contained no metal mines to 2640 ng L -1 in water taken directly from an abandoned mine shaft in Cornwall in England(Tatsi and Turner 2014), 120-570 ng L -1 in the Tunuyán River in Argentina(Escudero et al 2015).Therefore, in both of our investigated freshwater ecosystems, Tl concentrations in water are lower or in accordance with the range reported for world rivers.Thallium bioaccumulation and distribution in the intestine of brown trout (Salmo trutta) and Prussian carp(Carassius gibelio)…”
mentioning
confidence: 99%
“…Nielsen et al (2005) proposed the global average Tl range of 6±4 ng L -1 , based on analyses in 12 large rivers. Other studies reported various Tl concentration ranges in freshwater ecosystems, for example 5-17 ng L -1 in river waters in Poland (Karbowska 2016), 2-443 ng L -1 in United Kingdom(Law and Turner 2011) , about 13 ng L -1 in a river whose catchment contained no metal mines to 2640 ng L -1 in water taken directly from an abandoned mine shaft in Cornwall in England(Tatsi and Turner 2014), 120-570 ng L -1 in the Tunuyán River in Argentina(Escudero et al 2015).Therefore, in both of our investigated freshwater ecosystems, Tl concentrations in water are lower or in accordance with the range reported for world rivers.Thallium bioaccumulation and distribution in the intestine of brown trout (Salmo trutta) and Prussian carp(Carassius gibelio)…”
mentioning
confidence: 99%
“…206 It was found that Tl III was selectively adsorbed in the biomass at a pH of 7.0 while Tl I remained in solution. 206 It was found that Tl III was selectively adsorbed in the biomass at a pH of 7.0 while Tl I remained in solution.…”
Section: Thalliummentioning
confidence: 99%
“…The mineralization of biomass with strong inorganic acids is then required before metal determination. An alternative approach is to determine the metal content in the biomass by slurry sampling electrothermal atomic absorption spectrometry (SS-ETAAS) [38][39][40]. It allows to avoid the timeconsuming stage of biomass mineralization and reduces the risk of its contamination.…”
Section: Application Of Microorganisms In Chemical Analysismentioning
confidence: 99%
“…The most commonly used polymers are natural FAAS [62] Source: based on Refs. [40,[57][58][59][60][61][62] ETAAS electrothermal atomic absorption spectrometry, FAAS flame atomic absorption spectrometry, HG-AAS hydride generation atomic absorption spectrometry, HG-AFS hydride generation atomic fluorescence spectrometry, HG-ICP-OES hydride generation inductively coupled plasma optical emission spectrometry, ICP-MS inductively coupled plasma mass spectrometry, ICP-OES inductively coupled plasma optical emission spectrometry, LOD limit of detection, MT metallothioneins, UV-Vis ultraviolet-visible spectrophotometry, PF preconcentration factor compounds such as agar, agarose, gelatine, alginate, and carrageenan. Well-known method is the entrapment of biomass in alginate gels cross-linked with Ca 2+ ions, chitosan gels, alginate, and cellulose sulfate gels or cellulose acetate gels.…”
Section: Application Of Microorganisms In Chemical Analysismentioning
confidence: 99%